The emergence of piRNAs against transposon invasion to preserve mammalian genome integrity. Issue 1 (December 2017) - Ernst, Christina; Odom, Duncan; Kutter, Claudia
Abstract Transposable elements (TEs) contribute to the large amount of repetitive sequences in mammalian genomes and have been linked to species-specific genome innovations by rewiring regulatory circuitries. However, organisms need to restrict TE activity to ensure genome integrity, especially in germline cells to protect the transmission of genetic information to the next generation. This review features our current understandings of mammalian PIWI-interacting RNAs (piRNAs) and their role in TE regulation in spermatogenesis. Here we discuss functional implication and explore additional molecular mechanisms that inhibit transposon activity and altogether illustrate the paradoxical arms race between genome evolution and stability. Transposable elements can be activated during germ cell maturation, potentially leading to genome instability and rewiring of the genetic circuitry. In this review, the authors discuss how the piRNA machinery suppresses these elements to ensure accurate spermatogenesis.